Clinical Diagnosis of Mendelian Disorders Using a Comprehensive Gene-Targeted Panel Test for Next-Generation Sequencing - Okazaki, Tetsuya; Murata, Megumi; Kai, Masachika; Adachi, Kaori; Nakagawa, Naoko; Kasagi, Noriko; Matsumura, Wataru; Maegaki, Yoshihiro; Nanba, Eiji (YONAGO ACTA MEDICA, 2016)
[ABSTRACT] [Background] Genetic diagnoses provide beneficial information to patients and families. However, traditional genetic diagnoses are often difficult even for experienced clinicians and require recognition of characteristic patterns of signs or symptoms to guide targeted genetic testing for the confirmation of diagnoses. Next-generation sequencing (NGS) is a powerful genetic diagnostic tool. However, whole-genome and whole-exome sequencing (WES) are expensive, and the interpretation of results is difficult. Hence, target gene capture sequencing of gene panels has recently been applied to genetic diagnoses. Herein, we demonstrate that targeted sequencing approaches using gene panel testing are highly efficient for the diagnosis of Mendelian disorders. [Methods] NGS using TruSight one gene panel was performed in 17 families and 20 patients, and we developed a bioinformatic pipeline at our institution for detecting mutations. [Results] We detected causative mutations in 6 of 17 (35%) families. In particular, 11 (65%) families had syndromic diagnosis and 6 (35%) had no syndromic diagnosis before NGS testing. The number of positive diagnoses was 5 of 11 (45%) in the syndromic group and were 1 of 6 (17%) among patients of the no syndromic diagnosis group. [Conclusion] Diagnostic yields in the present study were higher than in previous reports of genetic and chromosomal tests and WES. The present comprehensive gene-targeted panel test is a powerful diagnostic tool for Mendelian disorders.